Peranan Pendidikan Keagamaan dalam Membentuk Kesiapan Remaja pada Pernikahan Usia Dini di Masyarakat Nelayan - Nur Alfina Sari Sitepu; Afrahul Fadhila Daulai; Sapri (Journal of Islamic Education Students (JIES), 2026)
Early marriage remains a serious social and educational issue in fishermen communities, especially when adolescents have not developed sufficient mental, moral, social, and spiritual readiness for family life. This study aims to analyze the role of religious education in shaping adolescents’ readiness for early marriage in the fishermen community of Kuala Lama Village. This research employed a qualitative phenomenological approach involving nine main informants, consisting of three adolescents who married at an early age and six parents, supported by religious and community figures. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings show that religious education is practiced through family habituation, Qur’an recitation, moral guidance, parental advice, mosque activities, Islamic learning groups, and community religious traditions. This study contributes by highlighting family-based religious education in coastal communities as a contextual framework for strengthening adolescents’ self-control, moral awareness, and responsibility before entering marriage.